SISTEM INFORMASI ANALISIS RASIO LIKUIDITAS PADA CV. MINAHASA - Hermes Engel Djohar; Syaiful Rahman; Afifah (KHARISMA Tech, 2018)
CV Minahasa is a service company engaged in the field of grief services, such as funeral homes, funeral equipment and supplies, delivery of corpses, and others. The need for large operational costs and the inability to finance the profits of the company, forcing CV Minahasa so far must continue to depend on the demand for business loans. The short-term credit demand continuously carried out by CV Minahasa without regard to the ability of the company's assets or assets to repay the credit caused a serious problem and almost made CV Minahasa fall bankrupt. Therefore, the purpose of this research is to create an information system application to analyze the ability of CV Minahasa to pay short-term credit using the liquidity ratio analysis method (which consists of working capital, current ratio, cash ratio, quick ratio, accounts receivable turnover and inventory turnover). This system was built using visual basic programming languages ​​through Visual Studio 2013. The results of this system showed that CV Minahasa experienced many difficulties for paying their short-term credit because it could only meet the current ratio number, while the quick ratio and cash ratio were quite bad. Dependency on the balance of the sufficient amount of cash, accounts receivable, and inventory (all assets) can be a serious threat because any time the company can go bankrupt because it is unable to pay its short-term credit.